Efficiency assessment of higher education institutions: Contradictions and paradoxes. Part II - Е. V. Romanov (Russian State Vocational Pedagogical University, 2020)
Introduction. The development of a clear and understandable strategy for the development of higher education, focused on training, which will be in demand by the modernised economy in the strategic perspective, is one of the conditions for the implementation of the Decree the President of the Russian Federation of 07 May2018. In this regard, the importance of an adequate efficiency assessment of the training system in general and in higher education is growing.Aim. In the context of the initiated discussion on methodological improvement of efficiency assessment of universities, the aims of the present article are the following: to discuss the existing criteria and indicators (proposed by the macro-regulator) of the expertise; to justify the inconsistency of such criteria and indicators to obtain real information on the innovative potential and the quality of human potential of graduates.Methodology and research methods. The research work was carried out on the basis of a systematic approach and inductive research method. To confirm the hypothesis, the method of comparative analysis and the following general scientific methods were applied: analytical review of scientific literature and normative documents, generalisation, comparison and analogy.Results and scientific novelty. Based on the performance monitoring data, the author presents the results of the evaluation of some universities, recognised as centers of innovation, technological and social development of the regions according to the indicators proposed by the Ministry of Education and Science. The conducted analysis indicates the complexity of the formulation of conclusions regarding the innovative potential of universities due to the incorrectness of the approach proposed by the macro-regulator. The shortcomings of the new project proposed by the Ministry of Science and Higher Education to assess the effectiveness of universities and their leaders are revealed. It is necessary to revise the methodology applied. When assessing university efficiency, principle focus should be emphasised on: a) identifying the fact and the dynamics of the increment of knowledge and skills of trainees (primarily, the degree of formation of abilities to learn and independently gain new knowledge); b) assessment of the economic component of the human potential of graduates, involving the introduction of indicators, by which it is possible to judge their demand in the labour market. Three measurement control points are proposed: the level of remuneration at the initial stage of career, in five and ten years after graduation. As a basic indicator of the university innovation activity, it is proposed to consider the share of the profits derived from the use of intellectual activity results in the total income of the organisation. In technical universities, this indicator can be used with additional indicators: number of patents per 100 scientific and pedagogical workers; the number of patents per 100 published articles indexed in the world scientometric databases. In order to maximise the potential of in-service teachers, the principles of financing universities should be changed, as well as the target rates should be introduced to attract young scientific and pedagogical personnel.Practical significance. The research results can be used to improve the methodology for efficiency assessment of universities, as well as to avoid the institutional traps in higher education and science.